TONI BLANK: A CASE STUDY OF THE LANGUAGE OF A SCHIZOPHRENE - HEDIYATI, TIKA NURAIDA (LANTERN (Journal on English Language, Culture and Literature), 2016)
Schizophrenia is one of the chronic mental disorders. Patients of schizophrenia cannotcommunicate with others properly. Also, they cannot produce good utterances syntactically andsemantically. This is caused by their language dysfunction. In this research, I am interested inanalyzing language dysfunction in schizophrenia. I choose Toni Blank‟s utterances in “ToniBlank Show Session One” as the object of my research. I focus on how schizophrenic‟s languagedysfunctions are classified and how these dysfunctions are being analyzed using linguisticframework. To analyze the data, I used Thought, Language, and Communication (TLC) scaleand cohesion coherence frameworks. The purpose of this study is to give linguistic analysisabout phenomena of language dysfunctions uttered by Toni Blank in “Toni Blank Show SessionOne”. The data used in this research are utterances which contain language dysfunctions fromthree episodes in “Toni Blank Show Session One”, entitled “Valentine Day”, “Teroris”, and“Sehat Ala Mas Toni”. I used purposive sampling to collect the data. In analyzing the data, I usedPadan and Agih methods by Sudaryanto (1993). To interpret the data, I used cohesion andcoherence framework. In 26 utterances which contain schizophrenic‟s language dysfunctions in“Toni Blank Show Session One”, I find that the language dysfunctions which are uttered by Toniare poverty of content, tangentiality, loss of goal, circumstantiality, illogicality, incoherence(word salad), neologism, clanging, echolalia, and self-reference. Poverty of speech, pressure ofspeech, distractibility, derailment, stilted speech, perseveration, and blocking are not found in thedata.